The effectiveness of a psychological-sports program to reduce aggression, anger and stubbornness among primary school students - عاصم امير فاضل أ.د عكلة سليمان علي (الرياضة المعاصرة)
The research problem lies in the presence of a group of pupils, which is a group of them have behavioral and emotional disorders For aggression, anger and stubbornness inside and outside the classroom, break times, therefore the idea of ​​a sports program that is compatible with the capabilities of the primary school and on the behavioral and emotional disturbed pupils during the physical education lesson and trying to change behavior. The goal of the research is to:Identify the level of behavioral and emotional disorders (aggression, anger, stubbornness) among primary school pupils.Preparing a sports psychological program to reduce behavioral and emotional disturbances for elementary school pupils.Exposing the effect of the psychological - sports program on the behavioral and emotional disorders of primary school pupils.    Therefore, the two researchers used the Experiment Research for its convenience and the nature of the research. The research sample reached (30) students who were divided into two control and experimental groups. The two researchers reached a number of conclusions, the most important of which are: